Clinical predictors of response to chemoradiotherapy for rectal cancer as an aid to organ preservation. Issue 6 (6th January 2021) - Fischer, Jesse; Eglinton, Tim W.; Frizelle, Frank A.
Abstract: Aim: Clinical predictors of pathological response to chemoradiotherapy for rectal cancer can influence patient management including selection for organ preservation. This study aimed to identify clinical predictors at a tertiary referral hospital. Methods: A retrospective review of clinical records was undertaken after identifying all patients with stage 1–3 rectal cancer treated with long course chemoradiotherapy and total mesorectal excision from 2013 to 2018. Clinicopathological factors were recorded and multivariate analysis performed to identify predictors of pathological complete response (pCR) and good response (AJCC TRG 0–1). Results: A total of 470 patients with rectal cancer were identified of which 164 met the inclusion criteria for the study. The pCR rate was 14.6% and good response (TRG 0–1) rate 43.7%. On univariate analysis, lower T stage, older age, node negative status, anterior tumour position and shorter tumour length on magnetic resonance imaging (MRI) were associated with good response (TRG 0–1). On univariate analysis cN stage, carcinoembryonic antigen <5 and shorter tumour length on MRI were associated with pCR. On binary logistic regression shorter length on MRI and lower clinical nodal stage were predictive of pCR and lower body mass index, anterior tumour position and higher haemoglobin were predictive of good response (TRG 0–1). Conclusion: Anterior tumour position is newly identified as an independent predictor of good response (TRG 0–1) to nCRT for rectal cancer and this should be explored in future studies. Higher haemoglobin and lower body mass index were also independent predictors of good response (TRG 0–1) and optimisation of these factors should be considered when using neoadjuvant chemoradiotherapy for rectal cancer. Abstract : A retrospective review and multi‐variate analysis of 164 patients treated with long‐course chemoradiotherapy and total mesorectal excision was performed to identify predictors of pathological response to neoadjuvant treatment. Longer tumour length on MRI and cN2 stage predicted not achieving pathological complete response. Lower BMI, anterior tumour position and higher haemoglobin predicted good response (TRG 0‐1).